The factors affecting the choice of undergraduate course of Miriam College High School students inputs on marketing strategy for the School of Library and Information Studies - Azcarraga, John Christopher E.
The University of the Philippines School of Library and Information Studies has always had a low freshmen (UPCAT passers) enrollment profile. Realizing the problem, the research aimed to rank pre-defined factors from previous literatures according to effect in selecting high school students' choice of undergraduate course. These ranking would be essential on future marketing plans for UP SLIS. The research utilized questionnaires for the survey on Miriam College High School. One hundred two (102) students were sampled, distributed among four year levels, grade 7 to 10. Results from the survey showed that the students from Miriam College High School Unit ranked 'personal preference' as their number one factor in choosing their undergraduate course. Students' choice of course lean towards the same field as their fathers. University of the Philippines, Ateneo de Manila, and University of Sto. Tomas were the top three chosen universities while Psychology, Business Administration, and Medicine were among the top three chosen courses. The results also showed that the students have low awareness on librarianship as an undergraduate course and as a career as well. The researcher recommended on using social media, other digital medium, org involvement, and external relations in marketing library science as an undergraduate course.